Návrh nosné konstrukce z železobetonu - Vlk, Adam (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Tato bakalářská práce se zabývá návrhem a statickým posouzením vybraných částí monolitických železobetonových nosných konstrukcí bytového domu s použitím metodiky BIM. Návrh proběhl v programu SCIIA Engineer a následně ověřen ručními výpočty, na základě výsledků z MKP byl stanoven optimální návrh vyztužení. Podle statického výpočtu se vytvořil digitální 3D model vyztužení, výkresová dokumentace a technická zpráva. Při návrhu konstrukcí se postupovalo podle platné normy ČSN EN 1992-1-1 - EC2.

This bachelor's thesis deals with the design and static assessment of selected parts of monolithic reinforced concrete load-bearing structures of an apartment building using the BIM methodology. The design was carried out in the SCIIA Engineer software and subsequently verified by manual calculations, based on the results from the FEM, the optimal reinforcement design was determined. According to the static calculation, a digital 3D model of reinforcement, drawing documentation and a technical report were created. The constructions were designed in accordance with the applicable standard ČSN EN 1992-1-1 - EC2.
Design of RC structure
Keywords: BIM (Building Information Modelling); křížem vyztužená železobetonová deska; železobetonové trámy; výpočtový model SCIA Engineer; digitální 3D model; BIM (Building Information Modelling); two-way reinforced concrete slab; reinforced concrete beams; SCIA Engineer calculation model; digital 3D model